Tests of representative firm models: results for German manufacturing industries - Bertrand M. Koebel (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
Many studies of producer behavior consider cost and input demand functions de-rived from microeconomic theory and estimate them on the basis of aggregate data. If firms' characteristics differs, the neglect heterogeneity can lead to estimation bias. An alternative is to restrict individual behavioral functions to be linear in the firm specific parameters. The aim of this paper is to describe aggregate producer behavior without placing too strong restrictions on the functional form and to explicitly take account of firm heterogeneity. Estimation for German manufacturing sectors confirms that ne-glected heterogeneity is an important source of bias in representative agent models.
Keywords: 330; exact aggregation; representative firm; heterogeneity; demand system